Total neoadjuvant therapy (TnT) with FOLFOX followed by short course radiation in locally advanced rectal cancer: A phase II study - Gim, Gahyun; Baran, Andrea M.; Wang, Wenjia; Zittel, Jason; Hezel, Aram F; Ramsdale, Erika E.; Badri, Nabeel; McGreevy, Maria; Qiu, Haoming; Mulkerin, Daniel; Temple, Larissa K. F.; Cellini, Christina; et al. (Journal of clinical oncology, 2024)
122Background: Total neoadjuvant therapy (TnT) is a new standard-of-care for locally advanced rectal cancer (LARC). Few prospective studies have evaluated specifically the use of chemotherapy and short course radiation (SCRT) in obtaining a complete clinical response (cCR) and offering non-operative management (NOM). This phase II study sequences FOLFOX followed by SCRT with the primary aim of evaluating the rate of cCR. Methods: Treatment-naïve adults with non-metastatic clinical T2-3N0 or T1-3 with N1-2a rectal adenocarcinoma were eligible to participate in this open label, single-arm clinical trial. Low rectal tumors defined as patients requiring abdominoperineal resection were excluded. This trial evaluated TnT with 5-fluorouracil, leucovorin and oxaliplatin (mFOLFOX6) every 2 weeks for 10-12 cycles followed by SCRT. SCRT consisted of 25 Gy in 5 fractions to rectal tumor and 20 Gy in 5 fractions to lymph node regions. Primary endpoint was the rate of cCR, defined as normal digital rectal exam (DRE) and endoscopic evaluation with normal appearing mucosa or scar but no nodularity or ulcerations. Near complete response (nCR) was defined as DRE with smooth or minor mucosal abnormalities and endoscopic exam with superficial ulceration or erythematous scar. Those with cCR or nCR after TnT were offered NOM and close surveillance; all others underwent total mesorectal excision (TME). Secondary endpoints included 1-year disease-free survival (DFS) from time of cCR (for NOM) or time of TME, overall survival (OS), and R0 surgical resection rate. Results: Twelve patients enrolled with a mean age 51.4 years; 7 were male. Mean distance of the primary tumor from the anal verge was 9.7 cm. Median duration of follow-up was 3.1 years. Three patients (25%) achieved cCR and 1 achieved nCR. All 4 with at least nCR underwent NOM per protocol. The patient with nCR had local regrowth and underwent TME and all 3 patients with cCR remain free of disease on NOM. In regards to secondary outcomes, 1-year DFS was 100%. Median OS was not reached. One patient had died at the time of analysis; this patient had lung nodules thought to be benign at enrollment but ultimately were deemed metastatic disease. All surgical resections were R0 with no local recurrence after TME. The study was closed early after published OPRA trial results demonstrated benefit of giving radiation first in TnT sequencing. Conclusions: Our study suggests that TnT with FOLFOX followed by SCRT may be a valid approach in treating LARC. In this small study, excellent local control was demonstrated with no local recurrence after TME and 25% of pts remaining on NOM at the time of analysis. The 33% of subjects offered NOM is much lower than the published 74% in OPRA, suggesting that chemo followed by SCRT may not be the most optimal approach if organ preservation is the primary treatment aim. Clinical trial information: NCT03781323.